MOTIVATION OF STUDENTS' INDEPENDENT WORK HIGHER INSTITUTIONS IN CONDITIONS CREDIT-MODULAR EDUCATION SYSTEM - V.V. Revenko (Academy of Cognitive and Natural Sciences, 2007)
The article is devoted to the problem of motivation of independent work of students under the conditions of module teaching. The significance of educational motivation in the process of studying is defined and its peculiarities are found out.